Crime Prevention Through Environmental Design: A Review on Potential Improvement in its Concept for a Safer City - Rozhan, Arinah; Yazid Mohd Yunos, Mohd (International Journal of Engineering and Technology, 2019)
The rise of crime in Malaysia is causing the people to live in a fear of crime. Criminals are even getting brave enough to commit crime in public areas. The purpose of this paper is to review the current Crime Prevention Through Environmental Design (CPTED) which is one of the effort for the Safe City Program in Malaysia. This study will analyze the effectiveness and weaknesses of CPTED and initiatives that can be done to improve it. This paper seeks to argue that the current CPTED approaches needs to have a critical thinking process to provide a safer living environment for the community. Based on content analysis, this paper reviews several theories and studies that has been done regarding approaches towards a safer city development. The findings from the previous studies are categorized by its strength (s) and weaknesses (w) in relation to the CPTED principles. The analysis concludes that CPTED can block crime from happening, but it does not stop the criminals from focusing on other places to commit crime. The result recommends to thoroughly improve one of the CPTEDâ€™s principles, which is the Community Development by using the language of built environment to enhance social engagement and development of behavior. Â Â